Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1463-1326.2006.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and decreased risk for obesity in the Atherosclerosis Risk in Communities Study

Abstract: These results suggest that variation within the LEP and MC4R genes is associated with reduced risk for obesity in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…[17][18][19][20][21][22] Because some studies used either small and/or selected samples and the criteria utilized to classify cases and controls differed largely, the relation between this SNP and type 2 diabetes Common SNPs in LEP and LEPR NY Souren et al and/or obesity is still unclear. Our data suggest that the LEP 19G4A SNP may be protective against cardiovascular disease, as G allele carriers have significantly higher HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22] Because some studies used either small and/or selected samples and the criteria utilized to classify cases and controls differed largely, the relation between this SNP and type 2 diabetes Common SNPs in LEP and LEPR NY Souren et al and/or obesity is still unclear. Our data suggest that the LEP 19G4A SNP may be protective against cardiovascular disease, as G allele carriers have significantly higher HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we therefore examined the effect of common SNPs in LEP and LEPR on birth weight and adult metabolic risk factors for type 2 diabetes measured in young twins recruited from the East Flanders Prospective Twin Survey (EFPTS). The SNPs studied have previously been associated with type 2 diabetesrelated traits in other populations, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and are either nonsynonymous or located in a region that might be of importance in the regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of I/G variant was further demonstrated to be related to gender, even though this variable did not affect the distribution of the LEP I/G genotypes. Accordingly, it has been shown that the association between a LEP variant (A19G) and risk for obesity was restricted to females from the Atherosclerosis Risk in Communities (ARIC) Study (35).…”
Section: Discussionmentioning
confidence: 99%
“…The LEPR polymorphisms (Lys 109 Arg, Gln 223 Arg and Lys 656 Asn) have been found to be either associated with [48,49,50] or not have any effect [51] on obesity or its anthropometric phenotype indicators. The LEP 19A→G polymorphism has been associated with obesity and leptin levels [18,52,53], while other studies reported a lack of association [20,54]. LD between the genotyped polymorphism and the causal one is reported to be one of the possible reasons for between-study heterogeneity.…”
Section: Discussionmentioning
confidence: 93%